Evaluation of Torlon Containers for Minimizing Radiation Exposure During Medical Isotope Production in a Research Reactor - Donald Nolting; Tristan Brannon; Rodrigo Viveros Duran; Joseph Lapka; Tracy Tipping; Mark Andrews; William Charlton (Health Physics, 2026)
The production of medical isotopes in research reactors often involves handling highly radioactive samples and containers, which poses a radiation exposure risk to personnel. This study evaluates the performance of Torlon 4203 polyamide-imide (PAI) containers as an alternative to traditional aluminum containers used in the central thimble (CT) experimental facility of The University of Texas at Austin (UT-Austin) Nuclear Engineering Teaching Laboratory (NETL) TRIGA Mark II reactor. Four irradiation experiments compared aluminum and Torlon containers with lead and graphite ballast configurations. Gamma and beta dose rates were measured after irradiation at multiple distances. Torlon containers demonstrated more than a 13-fold reduction in gamma dose rates relative to aluminum 15 hours after irradiation, maintained structural integrity for more than 150 hours of irradiation over multiple experiments, and provided a water-tight seal. These findings suggest that Torlon containers can substantially improve radiation safety and operational efficiency in isotope production settings.